2022
DOI: 10.26508/lsa.202101088
|View full text |Cite
|
Sign up to set email alerts
|

Refining the domain architecture model of the replication origin firing factor Treslin/TICRR

Abstract: Faithful genome duplication requires appropriately controlled replication origin firing. The metazoan origin firing regulation hub Treslin/TICRR and its yeast orthologue Sld3 share the Sld3-Treslin domain and the adjacent TopBP1/Dpb11 interaction domain. We report a revised domain architecture model of Treslin/TICRR. Protein sequence analyses uncovered a conserved Ku70-homologous β-barrel fold in the Treslin/TICRR middle domain (M domain) and in Sld3. Thus, the Sld3-homologous Treslin/TICRR core comprises its … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…This suggests that origin firing activity downstream of TRESLIN is important for its control of the cell cycle. Since TOPBP1 depletion failed to reproduce the effect of TRESLIN knockdown ( Figure 3 B), we depleted CDC45 instead, the major regulator of origin firing downstream of TRESLIN that also requires TRESLIN phosphorylations to be incorporated into active CMGs ( Ferreira et al., 2022 ). CDC45 depletion caused a reduction in DNA synthesis and the cell’s capacity to support origin firing, which was measured by the accumulation of RPA on chromatin (a surrogate of active forks) induced by ATR inhibition ( Figure S6 C) ( Toledo et al., 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that origin firing activity downstream of TRESLIN is important for its control of the cell cycle. Since TOPBP1 depletion failed to reproduce the effect of TRESLIN knockdown ( Figure 3 B), we depleted CDC45 instead, the major regulator of origin firing downstream of TRESLIN that also requires TRESLIN phosphorylations to be incorporated into active CMGs ( Ferreira et al., 2022 ). CDC45 depletion caused a reduction in DNA synthesis and the cell’s capacity to support origin firing, which was measured by the accumulation of RPA on chromatin (a surrogate of active forks) induced by ATR inhibition ( Figure S6 C) ( Toledo et al., 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…MTBP has been reported to be critical for the final step in the initiation of DNA replication and has been characterized as the metazoan ortholog to yeast Sld7 [ 5 ]. As shown in the bottom of Figure 1 , MTBP is reported to form a complex with Treslin, TopBP1, and cyclin-dependent kinase 8/19–cyclinC (Cdk8/19-cyclin C) that enables recruitment of Cdc45 to DNA, completing assembly of the activated replication helicase CMG (Cdc45-Mcm2-7-GINS) [ 71 , 72 ]. This process is enabled by the N-terminus of MTBP that associates with Treslin and the central domain that associates with Cdk8/19-cyclin C. The C-terminus, known in this context as the CTM, appears to function as a DNA binding domain [ 56 ].…”
Section: Mtbp In Dna Replicationmentioning
confidence: 99%
“…Surprisingly, the S7M-N domain turned out to be part of a beta-barrel fold that is structurally similar to the beta-barrel folds in Ku70 and Ku80 that mediate Ku70-Ku80 dimerization ( Figure 2 ) [ 99 , 100 ]. A similar Ku70/80-homologous beta-barrel fold is present in the M domain of Treslin/TICRR [ 99 ]. Mutating the Treslin/TICRR beta-barrel showed that it is required to bind MTBP [ 99 ].…”
Section: The Mtbp Origin Firing Factormentioning
confidence: 99%
“…A similar Ku70/80-homologous beta-barrel fold is present in the M domain of Treslin/TICRR [ 99 ]. Mutating the Treslin/TICRR beta-barrel showed that it is required to bind MTBP [ 99 ]. Together, these findings suggested two conclusions, (1) that MTBP/Sld7 and Treslin/TICRR/Sld3 are related by structure and (2) that they form a Ku70-Ku80-like heterodimer ( Figure 2 B).…”
Section: The Mtbp Origin Firing Factormentioning
confidence: 99%